Heterometallic Cube‐Type Molecular Nitrides. Issue 12 (6th April 2016) - Mena, Miguel; Pérez‐Redondo, Adrián; Yélamos, Carlos
Abstract: Polynuclear transition‐metal nitrido complexes constitute a class of molecular cage compounds with fascinating structures and interesting bonding properties. However, there is a lack of systematic strategies for the rational construction of aggregates with desired structures and compositions. This article provides a brief overview of the structure and bonding modes of polynuclear nitrido complexes, the most common synthetic approaches used to generate such aggregates, and a systematic review of the development of a family of heterometallic nitrido complexes with [MTi3 N4 ] cube‐type cores. The rational entry to those well‐defined systems is based on the incorporation of transition metals, lanthanides, and main‐group metals into the incomplete cube structure of the trinuclear titanium(IV) imido nitrido complex [{TiCp*(µ‐NH)}3 (µ3 ‐N)] (Cp* = η 5 ‐C5 Me5 ). The great versatility of [{TiCp*(µ‐NH)}3 (µ3 ‐N)] as a preorganized metalloligand is also confirmed by the preparation of complexes with heterometals in low (e.g., Mo 0, Ir I, and Pt 0 ) and high oxidation states (e.g., Zr IV, Ta V, and Pt IV ). Abstract : A wide family of heterometallic nitrido complexes with [MTi3 N4 ] cube‐type cores can be prepared by the incorporation of most of the metallic elements of the periodic table into the incomplete cube structure of [{TiCp*(µ‐NH)}3 (µ3 ‐N)] (Cp* = η 5 ‐C5 Me5 ).